Visual Guidance of Unmanned Aerial Manipulators - Santamaria-Navarro, Angel; Solà, Joan.; Andrade-Cetto, Juan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This monograph covers theoretical and practical aspects of the problem of autonomous guiding of unmanned aerial manipulators using visual information. For the estimation of the vehicle state (position, orientation, velocity, and acceleration), the authors propose a method that relies exclusively on the use of low-cost and highrate sensors together with low-complexity algorithms. This is particularly interesting for applications in which on board computation with low computation power is needed. Another relevant topic covered in this monograph is visual servoing. The authors present an uncalibrated visual servo scheme, capable of estimating at run time, the camera focal length from the observation of a tracked target. The monograph also covers several control techniques, which achieve a number of tasks, such as robot and arm positioning, improve stability and enhance robot arm motions. All methods discussed in this monograph are demonstrated in simulation and through real robot experimentation. The text is appropriate for readers interested in state estimation and control of aerial manipulators, and is a reference book for people who work in mobile robotics research in general.
I ntroduction -- Robot State Estimation -- Visual Servo -- Task Control -- Closing remarks.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Control, Robotics, Automation; Artificial Intelligence; Control and Systems Theory